Effects of Thermal Annealing on Structural and Optical Properties of Nanocrystalline Cd x Pb1-xS Thin Films Prepared by CBD - S. M. Ahmad; S. J. Kasim; L. A. Latif (Jordan Journal of Physics, 2025)
CdxPb1-xS Thin films with (x=0, 0.4) were successfully deposited on glass substrates using chemical bath deposition (CBD) method. It was confirmed from the X-ray diffraction (XRD) analysis that all the films exhibited a polycrystalline nature with preferential orientation along (200) plane. The deposited films were thermally annealed in order to investigate the effect of thermal annealing on the structural and optical properties. From the XRD analysis, better crystallization were observed with increasing crystallite size as the annealing temperature was raised from (298 to 573) k, while optical absorption measurements showed that the allowed direct band gap of the annealed samples decreased from 1.59 to 1.55 eV and 1.7 to 1.65 eV for PbS and Cd0.4Pb0.6S, respectively. Effect of thermal annealing on optical constants, such as extinction coefficient (k), refractive index (n),real and imaginary dielectric constants (Є1,Є2) were discussed. Each of the photo luminescence (PL) spectra revealed a single peak red emission around (680) nm for PbS and (670) nm for Cd0.4Pb0.6S. Keywords: Optical properties, Thin films, CBD, Thermal annealing, XRD. PACS: 79.60.Dp.